Questions   
Sort: 
 #1
avatar+177 
0
 #3
avatar+118654 
+2

\(n^3 = n + 3n(n - 1) + 6 \binom{n}{3}\)

 

Prove by induction for n>=3

 

Step 1

Prove true for n=3

LHS =27

RHS=27

So the statement is true of n=3

 

Step 2

Assume true for n =k where k is some integer greater or equal to 3

So this statement is true:

 

\(k^3=k+3k(k-1)+6\binom{k}{3}\\ k^3=k+3k^2-3k+6*\frac{k!}{(k-3)!3!}\\ k^3=3k^2-2k+\frac{k!}{(k-3)!}\\ k^3-3k^2+2k=\frac{k!}{(k-3)!}\\ \)

 

NOW prove that it will also be true for n=k+1

i.e.   Prove

 

\((k+1)^3=(k+1)+3(k+1)(k)+6\binom{k+1}{3}\\~\\ LHS=x^3+3k^2+3k+1\\~\\ RHS=k+1+3k^2+3k+6*\frac{(k+1)!}{3!(k-2)!}\\ RHS=3k^2+4k+1+\frac{(k+1)!}{(k-2)!}\\ RHS=3k^2+4k+1+\frac{k!(k+1)}{(k-3)!(k-2)}\\ RHS=3k^2+4k+1+\frac{k+1}{k-2}*\frac{k!}{(k-3)!}\\ sub\\ RHS=3k^2+4k+1+\frac{k+1}{k-2}*(k^3-3k^2+2k)\\ RHS=3k^2+4k+1+\frac{k+1}{k-2}*k(k^2-3k+2)\\ RHS=3k^2+4k+1+\frac{k+1}{k-2}*k(k-2)(k-1)\\ RHS=3k^2+4k+1+(k+1)*k(k-1)\\ RHS=3k^2+4k+1+k^3-k\\ RHS=k^3+3k^2+3k+1\\ RHS=LHS\)

 

So if it is true for n=k, it will be true for n=k+1

 

Step 3

The statement is true for n=3 so it is true for n=4, n=5, .....

Hence the statement is true for all integer values of n greater or equal to 3.

 

 

 

 

 

LaTex coding:

k^3=k+3k(k-1)+6\binom{k}{3}\\
k^3=k+3k^2-3k+6*\frac{k!}{(k-3)!3!}\\
k^3=3k^2-2k+\frac{k!}{(k-3)!}\\
k^3-3k^2+2k=\frac{k!}{(k-3)!}\\

 

(k+1)^3=(k+1)+3(k+1)(k)+6\binom{k+1}{3}\\~\\
LHS=x^3+3k^2+3k+1\\~\\
RHS=k+1+3k^2+3k+6*\frac{(k+1)!}{3!(k-2)!}\\
RHS=3k^2+4k+1+\frac{(k+1)!}{(k-2)!}\\
RHS=3k^2+4k+1+\frac{k!(k+1)}{(k-3)!(k-2)}\\
RHS=3k^2+4k+1+\frac{k+1}{k-2}*\frac{k!}{(k-3)!}\\
sub\\
RHS=3k^2+4k+1+\frac{k+1}{k-2}*(k^3-3k^2+2k)\\
RHS=3k^2+4k+1+\frac{k+1}{k-2}*k(k^2-3k+2)\\
RHS=3k^2+4k+1+\frac{k+1}{k-2}*k(k-2)(k-1)\\
RHS=3k^2+4k+1+(k+1)*k(k-1)\\
RHS=3k^2+4k+1+k^3-k\\
RHS=k^3+3k^2+3k+1\\
RHS=LHS

Nov 2, 2020
 #5
avatar+118654 
0
Nov 2, 2020

3 Online Users